Experimental implementation of direct-proportional length-based dna computing for numerical optimization of the shortest path problem - Ibrahim, Zuwairie; Tsuboi, Yusei; Ono, Osamu; Khalid, Marzuki (Old City Publishing, 2007)

(untitled)
DNA computing has emerged as an interdisciplinary field that draws together molecular biology, chemistry, computer science, and mathematics. The fundamental of this unconventional computation has been proven to solve weighted graph problems, such as the shortest path problem and the travelling salesman problem. One of the fundamental improvements in DNA computing is direct-proportional length-based DNA computing for the shortest path problem. Generally, in DNA computing, the DNA sequences used for the computation should be critically designed in order to reduce error that could occur during computation. In this paper, a procedure to design the DNA sequences for the direct-proportional length-based DNA computing is presented. The procedure includes DNASequenceGenerator, a graph-based approach for designing a set of good DNA sequences